Self-tuning fuzzy PID-nonsingular fast terminal sliding mode control for robust fault tolerant control of robot manipulators - Van, Mien; Do, Xuan Phu; Mavrovouniotis, Michalis (ISA transactions, 2020)
In this work, a new robust controller is developed for robot manipulator based on an integrating between a novel self-tuning fuzzy proportional–integral–derivative (PID)-nonsingular fast terminal sliding mode control (STF-PID-NFTSM) and a time delay estimation (TDE). A sliding surface based on the PID-NFTSM is designed for robot manipulators to get multiple excited features such as faster transient response with finite time convergence, lower error at steady-state and chattering elimination. However, the system characteristics are hugely affected by the selection of the PID gains of the controller. In addition, the design of the controller requires an exact dynamics model of the robot manipulators. In order to obtain effective gains for the PID sliding surface, a fuzzy logic system is employed and in order to get an estimation of the unknown dynamics model, a TDE algorithm is developed. The innovative features of the proposed approach, i.e., STF-PID-NFTSM, is verified when comparing with other up-to-date advanced control techniques on a PUMA560 robot. •A novel self-tuning fuzzy PID-NFTSM (STFPID-NFTSM) and time delay estimation (TDE) is developed.•The proposed controller possesses faster transient response, lower steady state error, guarantees a finite time convergence.•The stability of the closed-loop hybrid system is demonstrated based on Lyapunov function.•Compared to other state-of-the-art controllers, the proposed method has superior performance.